2013
DOI: 10.1063/1.4818167
|View full text |Cite
|
Sign up to set email alerts
|

Linking molecular level chemistry to macroscopic combustion behavior for nano-energetic materials with halogen containing oxides

Abstract: Coupling molecular scale reaction kinetics with macroscopic combustion behavior is critical to understanding the influences of intermediate chemistry on energy propagation, yet bridging this multi-scale gap is challenging. This study integrates ab initio quantum chemical calculations and condensed phase density functional theory to elucidate factors contributing to experimentally measured high flame speeds (i.e., >900 m∕s) associated with halogen based energetic composites, such as aluminum (Al) and iodine pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Shimojo et al [29][30][31] used the first-principles molecular dynamics to study electronic transportation during reaction process of Al/Fe 2 O 3 nanothermite. Farley et al [32] integrated ab initio quantum chemical calculations and condensed phase density functional theory to illustrate reasons leading to experimentally measured high flame speeds, and found that activation energy correlated with flame speed rather than heat of combustion. Furthermore, Nguyen et al [33,34] reported molecular dynamic study for Al/Pd core-shell nanoparticles and reaction rate is determined by the solid-state diffusion of Al atoms.…”
Section: Introductionmentioning
confidence: 97%
“…Shimojo et al [29][30][31] used the first-principles molecular dynamics to study electronic transportation during reaction process of Al/Fe 2 O 3 nanothermite. Farley et al [32] integrated ab initio quantum chemical calculations and condensed phase density functional theory to illustrate reasons leading to experimentally measured high flame speeds, and found that activation energy correlated with flame speed rather than heat of combustion. Furthermore, Nguyen et al [33,34] reported molecular dynamic study for Al/Pd core-shell nanoparticles and reaction rate is determined by the solid-state diffusion of Al atoms.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, to their high iodine content, these oxidizers have a high enthalpy of reaction and high flame temperature when used as part of an Al-based pyrolant mixture (Table S1). Notably, Al/I 2 O 5 has the highest iodine content (67 wt-%) and a high reactivity [19,20]. However, the hygroscopic nature of I 2 O 5 can negatively impacting reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…7 Because these high bulk density films have limited porosity, gas generating oxidizers may inhibit the diffusion of energy through the film and hinder flame speed. This makes KClO 4 a desirable oxidizer 16 because of its high oxygen content and its low gas generation. Farley et al 6 also showed that Al + KClO 4 produced orders of magnitude slower flame speeds in comparison to Al with other solid oxidizers (e.g., silver iodate, calcium iodate and iodine pentoxide ) indicating that Al + KClO 4 is not particularly reactive.…”
Section: Compositionmentioning
confidence: 99%
“…Farley et al 16 examined the combustion properties of Al + KClO 4 and found this mixture to be relatively non-gas generating compared to thermites such as Al + I 2 O 5 , 16 Al + MoO 3 , 8,17 and Al + CuO. 7 Because these high bulk density films have limited porosity, gas generating oxidizers may inhibit the diffusion of energy through the film and hinder flame speed.…”
Section: Compositionmentioning
confidence: 99%
See 1 more Smart Citation